2016
DOI: 10.2298/tsci130621052k
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the effect of insulation on heat transfer of thermal bridges with different types

Abstract: In the present study, the effects of different types thermal bridges formed by beams for floor-wall junctions in reinforced concrete structures, with and without balconies, and the optimum configuration of the insulation layers to avoid heat loss were investigated as numerically. Both insulation between the walls and internal insulation was selected for floor-wall junctions and internal insulation was used for floor-wall junctions with balcony. Fluent package program was used to solve the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Results indicate that both the heat loads and cooling magnitude have strong influences on the thermal performance of the TSVC, and the thermal resistance in the extended section occupies most proportion of the overall thermal resistance of the TSVC. When the heat load is 15.84 W, the proportion of 18 Th Tch R − in the overall thermal resistance of the TSVC is in the range of 75.8%~92.4% for different cooling fan voltages, while 18 Tc Tch R − takes over only 7.59%~24.18%. Experiment results also suggest that the overall thermal resistance of the TSVC increases with the increase of heat loads and cooling fan voltage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results indicate that both the heat loads and cooling magnitude have strong influences on the thermal performance of the TSVC, and the thermal resistance in the extended section occupies most proportion of the overall thermal resistance of the TSVC. When the heat load is 15.84 W, the proportion of 18 Th Tch R − in the overall thermal resistance of the TSVC is in the range of 75.8%~92.4% for different cooling fan voltages, while 18 Tc Tch R − takes over only 7.59%~24.18%. Experiment results also suggest that the overall thermal resistance of the TSVC increases with the increase of heat loads and cooling fan voltage.…”
Section: Discussionmentioning
confidence: 99%
“…The influences of heat loads and cooling capability of heat sink were considered. Numerical model has also been proposed based on FLUENT [16,18,19], to investigate the thermal hydrodynamic characteristics of the working fluid inside the TSVC. The results obtained in this paper could provide references on improving the thermal performance of this TSVC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, the same research group published another research study [22]. The objectives of this research were the same as the previous one, but the study was extended to different building and insulation materials.…”
Section: Sun-shade Elementmentioning
confidence: 99%
“…The direct 2D and 3D method of building energy simulation are complex as well as need greater computing capacity. Another study by (Karabulut et al,2016) showed that increasing insulation layers on the exterior helps way better to reduce the thermal bridges. To see the results different configurations were taken and insulating layers were applied to the same geometry.…”
Section: Introductionmentioning
confidence: 99%